PENDAPATAN DAN TINGKAT KESEJAHTERAAN PETANI PADI SAWAH DI KABUPATEN LAMPUNG TENGAH - Prasetio, Dwi Ega; Widjaya, Sudarma; Murniati, Ktut (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2020)
This reseacrh aimed at analyzing level of income and welfare of rice farmers in Central Lampung Regency. The reseacrh was conducted in Central Lampung District, deliberately taken location with consideration that it is the largest rice production center in Lampung Province in 2016. Data were collected in January 2018 using a survey method. The sample in this study amounted to 66 respondents of lowland rice farmers taken using a simple random sampling. Data were analyzed using income analysis, R-C ratio, and household welfare according to the 2014 BPS criteria. The results showed that the contribution of the income of lowland rice farmers in Central Lampung Regency in 2016 amounted to 70.81 percent of the total household income, the rice farmers in Central Lampung Regency are mostly in the prosperous category based on the 2014 BPS criteria. Key words: income, rice farmers, welfare